2021
DOI: 10.1093/clinchem/hvab060
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of LC-MS/MS Measurements of Plasma Free Normetanephrine, Metanephrine, and 3-Methoxytyramine

Abstract: Background Plasma-free normetanephrine and metanephrine (metanephrines) are the recommended biomarkers for testing of pheochromocytoma and paraganglioma (PPGL). This study evaluated the status of harmonization of liquid chromatography-tandem mass spectrometry-based measurements of plasma metanephrines and methoxytyramine and clinical interpretation of test results. Methods 125 plasma samples from patients tested for PPGLs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
(46 reference statements)
2
13
0
Order By: Relevance
“…The normetanephrine and metanephrine concentrations in the 53 clinical plasma samples measured by the four routine assays and cRMP were compared using PB and BA analyses. Similar to previous findings [ 18 ], we observed good correlations between the cRMP and routine assays. Notably, we previously demonstrated that using patient-derived plasma samples assigned by the cRMP to recalibrate routine assays greatly decreased the large biases of the routine assays [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…The normetanephrine and metanephrine concentrations in the 53 clinical plasma samples measured by the four routine assays and cRMP were compared using PB and BA analyses. Similar to previous findings [ 18 ], we observed good correlations between the cRMP and routine assays. Notably, we previously demonstrated that using patient-derived plasma samples assigned by the cRMP to recalibrate routine assays greatly decreased the large biases of the routine assays [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…Plasma NMN concentrations in PCC dogs were markedly lower in our study than in previous studies, 13,14 whereas pMN concentrations were moderately lower to comparable. Similar to our study, LC‐MS/MS was used for free metanephrine measurement in both previous studies, which demonstrates good agreement among different laboratories 25 . The difference in metanephrine concentrations might be explained by the fact that, today, PCCs are diagnosed earlier in the course of the disease because of increasing awareness of this disease among clinicians and increasing use of diagnostic imaging.…”
Section: Discussionsupporting
confidence: 83%
“…A limitation of our study is that plasma free metanephrines of dogs with PCC, HC and NAI were measured by a different laboratory than the laboratory that was used for the reference population. However, both laboratories used LC‐MS/MS for metanephrine measurements, which has been shown to provide comparable results among laboratories 25 …”
Section: Discussionmentioning
confidence: 99%
“…Based on measurements of plasma MTY, at least a third of HNPGLs in our cohort were identified as biochemically active, which is similar to previous findings ( van Duinen et al 2013 , Smith et al 2021 ). However, most current methods of analysis do not reliably measure MTY at the concentration range necessary to establish the production of the metabolite by small tumors typical of HNPGLs ( Peitzsch et al 2021 ). An exception might be the recently described LC-MS/MS method described by van Faassen et al by which the use of in situ derivatization enables highly sensitive measurements of plasma MTY and other metabolites in as little as 50 µL of plasma ( van Faassen et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%